PENERAPAN BAURAN PEMASARAN (MARKETING MIX) SEBAGAI STRATEGI PEMASARAN PRODUK GULO PUAN DESA BANGSAL - Dewi Sartika; Imelda Saluza; Roswaty Roswaty (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
Gulo puan is one of the indigenous cuisines from the district of Pampangan, Regency of Ogan Komering Ilir (OKI), South Sumatra. Gulo means sugar and Puan  means milk. Gulo Puan is made from sugar and caramel milk. The milk used in making gulo puan is from swamp buffalo. Gulo puan is very popular in several regions in South Sumatra. However, not many people are familiar with gulo puan like other typical South Sumatra cuisines. The team from the Indo Global Mandiri University (UIGM) carried out a Stimulus Community Partnership Program activity funded by the Ministry of Technology, Research and Higher Education Republic of Indonesia in order to provide solutions to the target partners namely Gulo Puan Business group in Bangsal Village by implementing the Marketing Mix. Improving product quality is conducted through making logos and product packaging labels, using stand pouch packaging and plastic jars, and fascinating innovation in the form of gulo puan candy products (Puan Candy). Promotion and distribution channels are increased by marketing the products through e-commerce to reach consumers widely and bypassing distribution channels, while an increase in price stays is conducted by providing products with various weight variations, ranging from 100 grams to 1000 grams. Based on the results of the analysis, it could be stated that the product, price, promotion and location or place (distribution channel) of consumer loyalty in re-buying gulo puan products could be seen from all the significance values of the independent variables  that is less than 0.05.